The Effect Of Project Based Learning Model (PJBL) On The Character And Learning Outcomes Of Students In Ips Subjects Class VIII Smp Negeri I Bontolempangan Gowa District - Pirdaus, Pirdaus; Rahman, Nawir; Saripuddin (International Journal of Technology and Education Research, 2025)
This study aims to analyse the effect of the Project-Based Learning (PjBL) model on the character and learning outcomes of students in Social Studies (IPS) in Grade VIII at SMP Negeri 1 Bontolempangan, Gowa Regency. This study used a quantitative approach with an experimental design on 22 Grade VIII A students selected through purposive sampling. Data were collected through observation, questionnaires, and documentation, then analysed using descriptive and inferential statistics (multiple regression and MANOVA). The results of the study indicate that the implementation of the PjBL model significantly improves students‘ character, particularly in terms of discipline, responsibility, cooperation, creativity, and empathy. Additionally, the PjBL model also has a significant positive impact on improving students’ learning outcomes in Social Studies. Multivariate analysis reinforced the findings that the PjBL model simultaneously had a significant effect on the development of students' character and learning outcomes, with a significance value of < 0.05 on all statistical indicators used. These findings confirm that PjBL is effective in building character and improving student learning outcomes holistically in social studies learning. Therefore, the integration of project-based learning models is recommended to support the achievement of more comprehensive educational goals.